Towards analysing user attention using electroencephalography in immersive multisensory virtual environments - Silva, Carla Estefany Caetano; Vieira, Rômulo; Trevisan, Daniela Gorski; Muchaluat-Saade, Débora C. (Proceedings of the ACM International Conference on Interactive Media Experiences Workshops (IMXw); 2025: Proceedings of the ACM International Conference on Interactive Media Experiences WorkshopsDO - 10.5753/imxw.2025.2092, 2025)
This study explores attention detection using EEG signals and its application in immersive environments, combining insights from different approaches. We assessed the attention levels of 12 participants through 2D digital games, highlighting that tasks without time limitswere more effective in maintaining user engagement.We intend to run another experiment with PhysioDrum, a multisensory drum system that combines physical and digital elements for immersive musical experiences. Equipped with sensors and actuators, PhysioDrum ensures real-time synchronization and multimodal feedback, demonstrating potential for creative and educational uses. Future research aims to analyze the interaction between attention and immersive environments, focusing on the differences in engagement between neurotypical and neurodivergent users, and promoting the development of therapeutic tools for cognitive and emotional enrichment.